Identification of STOP1-Like Proteins Associated With Aluminum Tolerance in Sweet Sorghum (Sorghum bicolor L.) - Huang, Sheng; Gao, Jie; You, Jiangfeng; Liang, Yanan; Guan, Kexing; Yan, Siqi; Zhan, Meiqi; Yang, Zhenming (Frontiers in Plant Science, 2018)
Aluminum (Al) toxicity in acidic soils affects crop production worldwide. C2H2-type zinc finger transcription factor STOP1/ART1-mediated expression of Al tolerance genes has been shown to be important for Al resistance in Arabidopsis, rice and other crop plants. Here, we identified and characterized four STOP1-like proteins (SbSTOP1a, SbSTOP1b, SbSTOP1c and SbSTOP1d) in sweet sorghum, a variant of grain sorghum (Sorghum bicolor L.). Al induced the transcription of the four SbSTOP1 genes in both time- and Al concentration-dependent manners. All SbSTOP1 proteins localized to the cell nucleus, and they showed transcriptional activity in a yeast expression system. In the HEK 293 coexpression system, SbSTOP1d showed transcriptional regulation of SbSTAR2 and SbMATE, indicating the possible existence of another SbSTOP1 and SbSTAR2-dependent Al tolerance mechanism in sorghum apart from the reported SbMATE-mediated Al exclusion mechanism. A transgenic complementation assay showed that SbSTOP1d significantly rescued the Al-sensitivity characteristic of the Atstop1 mutant. Additionally, yeast two-hybrid and BiFC assays showed that SbSTOP1d interacted with SbSTOP1b and SbSTOP1d itself, suggesting that SbSTOP1 may function as a homodimer and/or heterodimer. These results indicate that STOP1 plays an important role in Al tolerance in sweet sorghum and extend our understanding of the complex regulatory mechanisms of STOP1-like proteins in response to Al toxicity.